On the Convergence of Implicit Difference Schemes for Hyperbolic Conservation Laws (Journal of Computational Mathematics, 2002)
This paper is to treat implicit difference approximations to hyperbolic conservation laws with non-convex flux. The convergence of the approximate solution toward the entropy solution is established for the general weighted implicit difference schemes, which include some well-known implicit and explicit difference schemes.
Keywords: Conservation laws; weighted implicit schemes; entropy solution.